Synthesis of New Isolated Pyrazolo, Isoxazolo Derivatives Incorporating Pyrido[1,2]thiazinoquinoline: Advanced Study - Nadia A. A. Elkanzi (Current Advances in Chemistry and Biochemistry Vol. 5, 2021)
2,9-diacetyl-7,14-diamino-5,5a,6a,7,12,12a-hexahydro-[1,2]thiazino[4’,5’:5,6]pyrido[2,3-g][1,2]thiazino[5,4-b]quinoline-1,6,8,13(2H,4H,9H,11H)-tetraone(2) was prepared by treatment of ,14-diamino-5,5a,12,12a-tetrahydro [1,2]thiazino[4’,5’:5,6]pyrido[2,3-g][1,2] thiazino[5,4-b]quinoline-1,6,8,13(2H,4H,9H,11H)-tetraone (1) with acetic anhydride and glacial acetic acid, The reaction of thiazino quinoline (2) with aromatic aldehyde (3a-c) and piperdine catalyst provide arylidene derivatives( 4a-c). N-acetylpyrazolo- derivatives (5a-c) and N-phenylpyrazolo derivatives (6a-c) were prepared via reaction of arylidene derivatives (4a-c) with an equimolar amount of hydrazine hydrate and/or phenylhydrazine in base catalyst. Also reaction of arylidene derivatives (4a-c) with an equimolar amount of hydroxylamine hydrochloride in ethanol with the presence of sodium hydroxide as a catalyst afford the corresponding isooxazolo pyrimidine derivatives(7a-c).The structure of the synthesized compounds were established by spectroscopic analysis (IR, 1H-NMR,13CNMR and MS) and elemental analysis.